Health promotion in stunting prevention efforts in South Kluet, South Aceh - Said Usman; Tarkhi Tarkhi; Ismail Ismail (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The Government of Indonesia has made stunting one of the priority health problems that must be dealt with seriously. Stunting in South Aceh in 2022 is 34,8%, which will decrease to 5,03% in 2023. However, this figure is still below the target value. This study aimed to explore health promotion through stunting prevention efforts in South Kluet, South Aceh. This study uses a qualitative method with purposive sampling. Data collection involved in-depth interviews and observations. The research was conducted in South Kluet District, South Aceh Regency, in May–July 2024. The informants were the head of the health office, sub-district head, and head of the health center. The data were analyzed using inductive content analysis methods. The results of the study show several themes, namely, improving the nutritional quality of individuals, families, and communities, taking joint action, health and nutrition education strategies through family independence, accelerating stunting reduction carried out through the healthy living community movement, the first 1000 days of life movement to accelerate stunting reduction, implementation in stunting reduction, and obstacles in the implementation of stunting reduction. In conclusion, health promotion in the implementation of stunting prevention has been going well, but needs to increase socialization efforts are required to prevent stunting.